Diffusive transport of nanoscale objects through cell membranes: a computational perspective. Issue 16 (1st April 2020) - Xu, Ziyang; Gao, Lijuan; Chen, Pengyu; Yan, Li-Tang
Abstract : Clarifying the diffusion dynamics of nanoscale objects with cell membrane is critical for revealing fundamental physics in biological systems. This perspective highlights the advances in computational and theoretical aspects of this emerging field. Abstract : Diffusion is an essential and fundamental means of transport of substances on cell membranes, and the dynamics of biomembranes plays a crucial role in the regulation of numerous cellular processes. The understanding of the complex mechanisms and the nature of particle diffusion have a bearing on establishing guidelines for the design of efficient transport materials and unique therapeutic approaches. Herein, this review article highlights the most recent advances in investigating diffusion dynamics of nanoscale objects on biological membranes, focusing on the approaches of tailored computer simulations and theoretical analysis. Due to the presence of the complicated and heterogeneous environment on native cell membranes, the diffusive transport behaviors of nanoparticles exhibit unique and variable characteristics. The general aspects and basic theories of normal diffusion and anomalous diffusion have been introduced. In addition, the influence of a series of external and internal factors on the diffusion behaviors is discussed, including particle size, membrane curvature, particle–membrane interactions or particle-inclusion, and the crowding degree of membranes. Finally, we seek to identify open problems in the existing experimental, simulation, and theoretical research studies, and to propose challenges for future development.